Development of an open source web-based infrastructure for designing medical devices - Mortimer, Kenneth (Cranfield University, 2009)
The term ‘Open Source’ is commonly associated with software due to its proven success, encompassing a user’s ability to review and modify the underlying source code, to disseminate modified or unmodified versions to others, and to use it without facing the prospect of legal repercussions (Siedlok, 2001). In the context of product design, namely medical device design, the concept remains relatively novel with no prior research being reported. A study of applying the open source concept to medical device design by developing a web based infrastructure for its facilitation is reported here. Results: The stakeholder requirements are captured using a semi-structured questionnaire and validated through cross referencing responses to questions with other responses from stakeholders of the same or similar occupation. The most prominent responses are selected as the key stakeholder requirements and utilised in conjunction with the functional system requirements outlined in the System Requirements Specification (SyRS), both sets of requirements provide the foundation for the open source web based infrastructure development. Conclusion: The comprehensiveness of the requirements indicate that the open source web based infrastructure will support the design of all medical devices that are classified as high risk, medium risk or low risk devices, whilst devices external to this scope remain a future certainty.